SPECIFICITY OF TRANSLATING MEDIA AND INTERNET TEXTS (USING THE EXAMPLE OF RUSSIAN AND UZBEK LANGUAGES) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Article devoted to the study of the specifics of translating media and internet texts between Russian and Uzbek. The work examines the theoretical foundations of translating such texts, identifies their genre and functional features, and analyzes lexical, grammatical, and cultural challenges in translation. A practical analysis of news articles and social media posts was conducted, typical translation errors were identified, and recommendations were proposed to improve translation quality. The study demonstrates that successful translation of media and internet texts requires not only linguistic competence but also knowledge of genre conventions, media specificity, and internet context.